2005
DOI: 10.1177/003335490512000107
|View full text |Cite
|
Sign up to set email alerts
|

Personal Use of Hair Dyes and the Risk of Bladder Cancer: Results of a Meta-Analysis

Abstract: SYNOPSISObjective. This study examined the methodology of observational studies that explored an association between personal use of hair dye products and the risk of bladder cancer.Methods. Data were pooled from epidemiological studies using a general variancebased meta-analytic method that employed confidence intervals. The outcome of interest was a summary relative risk (RRs) reflecting the risk of bladder cancer development associated with use of hair dye products vs. non-use. Sensitivity analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 21 publications
2
40
0
2
Order By: Relevance
“…Results for bladder cancer risk from studies of occupationally exposed populations, such as barbers or hairdressers, are inconsistent with no associations or weak associations reported in some studies [2,7,8], and positive associations reported in other studies [9]. Recently, the possible association of personal hair dye use with bladder cancer has been examined in two published meta-analyses by Huncharek and Kupelnick [10] and Takkouche et al [11]. Although these publications reviewed nearly the same set of studies, the conclusions of the authors differed with respect to the potential risk of bladder cancer and personal hair dye use.…”
Section: Introductionmentioning
confidence: 99%
“…Results for bladder cancer risk from studies of occupationally exposed populations, such as barbers or hairdressers, are inconsistent with no associations or weak associations reported in some studies [2,7,8], and positive associations reported in other studies [9]. Recently, the possible association of personal hair dye use with bladder cancer has been examined in two published meta-analyses by Huncharek and Kupelnick [10] and Takkouche et al [11]. Although these publications reviewed nearly the same set of studies, the conclusions of the authors differed with respect to the potential risk of bladder cancer and personal hair dye use.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent metaanalyses yielded contradictory conclusions, one found a pooled relative risk of 1.01 (95% CI, 0.89-1.14; ref. 5) and the other concluded that there was a 22% to 50% increased bladder cancer risk for permanent hair dye users (6). However, the latter report did not include the most recent negative casecontrol study (10) and the pooled significant ORs were obtained by excluding selected studies that the authors deemed questionable in study design.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that almost any hair dye on the market contains small amounts of aromatic amines and that aromatic amines are carcinogenic in animals (2, 3) has generated great interest in studying the association between hair dye use and cancer risk, especially bladder cancer risk. Although occupational exposure to hair dyes by hairdressers and barbers has been shown to increase bladder cancer risk in a number of epidemiologic studies (4), whether or not personal hair dye use may increase bladder cancer risk remains controversial with fewer studies published and fewer cases and exposed individuals (4)(5)(6). In this study, we used one of the largest bladder cancer case-control studies to evaluate the association between personal hair dye use and bladder cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Another population-based case-control study involving 897 cases and equal number of controls found a two-fold increased risk of bladder cancer among women who had used permanent hair dyes at least once a month, and the risk increased to 3.3-fold (95% CI: 1.3,8.4) for women who were regular (at least monthly) users for at least 15 years (15). The cohort studies generally reported no association between bladder cancer and hair dye use (16)(17)(18)(19)(20) Three meta-analysis studies have been published since 2005 assessing risk of bladder cancer and exposure to hair dyes (21)(22)(23). A study by Huncharek and Kupelnick (21), which had significant exclusion criteria (which limited the meta-analysis to a mere seven studies) and a unique weighted method of analyzing the data, suggested that there is a relative risk between 1.22 (95% CI: 1.11, 1.51) and 1.50 (95% CI: 1.30, 1.98).…”
Section: Bladder Cancermentioning
confidence: 99%
“…The cohort studies generally reported no association between bladder cancer and hair dye use (16)(17)(18)(19)(20) Three meta-analysis studies have been published since 2005 assessing risk of bladder cancer and exposure to hair dyes (21)(22)(23). A study by Huncharek and Kupelnick (21), which had significant exclusion criteria (which limited the meta-analysis to a mere seven studies) and a unique weighted method of analyzing the data, suggested that there is a relative risk between 1.22 (95% CI: 1.11, 1.51) and 1.50 (95% CI: 1.30, 1.98). Another two meta-analysis studies by Takkouche et al (22) and Kelsh et al (23) found no association between bladder cancer and hair dye use.…”
Section: Bladder Cancermentioning
confidence: 99%